Analisis Kesesuaian Biaya Terapi Pasien Stroke Iskemik Rawat Inap terhadap Tarif INA-CBGs Di Magelang - Suzan Astyamalia; Mir-a Kemila; Wahid Sabaan (Yayasan Literasi Sains Indonesia, 2026)
Ischemic stroke is catastrophic diseases and recognized as placing a considerable financial strain on patients and health systems. The difference between actual hospital expenditures and INA-CBGs reimbursement rates potentially threaten the financial stability of healthcare facilities. Therefore, this study aimed to analyze the comparison between actual hospital costs and INA-CBGs tariffs for hospitalized ischemic stroke patients covered by the National Health Insurance, using a retrospective approach based on medical record and JKN claim data obtained from ischemic stroke patients at Soerojo Hospital in 2025. A total of 217 patients met the inclusion criteria, and the analysis was conducted based on ward class and severity level to calculate the difference between actual costs and INA-CBGs tariffs. The results indicated at severity level 1, all ward classes yielded a positive difference (surplus), namely IDR 3,342,519 (class 1), IDR 3,068,501 (class 2), and IDR 1,486,293 (class 3). In contrast, at severity level 2, all classes recorded a negative difference (deficit) of IDR 1,062,231, IDR 2,377,175, and IDR 2,191,417, respectively. The deficit widened considerably at severity level 3, with negative differences of IDR 22,515,300 (class 1), IDR 7,634,467 (class 2), and IDR 18,819,214 (class 3). Therefore, an evaluation and adjustment of INA-CBGs tariffs are warranted to ensure that the reimbursement rates better reflect the actual cost of hospital care.